Cultural awareness among first-year undergraduate students of English and translation - Zupan, Simon (ELOPE (Ljubljana), 2020)
The article presents the results of a culture quiz that was administered among undergraduate students of English and Translation at the University of Maribor in 2019. Comprising twenty items from five domains of culture that the respondents had to identify, the results of the quiz showed that that the students were most familiar with items from the domains of technology and its closely related vocabulary, followed by sports, politics and high culture (drama, literature, ballet). The study also suggested some differences based on respondents' gender and their high school grade performance in English. The results partly overlap with the results of a similar study from 2007, corroborating that popular culture remains the most recognizable cultural domain among the surveyed students.
Keywords: anglistika in prevajalstvo; cultural awareness; English and translation studies; kulturna ozaveščenost; kviz; quiz; raziskava; students; survey; študenti